Cervical isometric strength and range of motion of elite rugby union players: a cohort study - Hamilton, D. F.; Gatherer, D. (BMC Sports Science, Medicine and Rehabilitation, 2014)
Background: Head and neck injury is relatively common in Rugby Union. Despite this, strength and range-of-motion characteristics of the cervical spine are poorly characterised. The aim of this study was to provide data on the strength and range-of-motion of the cervical spine of professional rugby players to guide clinical rehabilitation.